A Rare Case Report of NEHI in a Preterm Infant with Review of the Literature - Chetna Mangat; Mikaela DeCoster; Natasa Milosavljevic; Lisa Hiskey; Elizabeth H. Ristagno; Nadir Demirel (Case Reports in Pediatrics)
Background. Neuroendocrine cell hyperplasia of infancy (NEHI) is a rare respiratory disorder. During infancy, it typically presents with hypoxemia, tachypnea, and respiratory distress, and is commonly misdiagnosed as common childhood illnesses such as pneumonia, reactive airway disease, or bronchiolitis. Lack of awareness about this relatively new and rare disorder in primary care and acute care settings lead to delayed diagnosis and unnecessary use of antibiotics. Case Presentation. We present a case of a 7-month-old girl, born prematurely at 32 weeks with tachypnea and respiratory distress who was initially diagnosed with viral pneumonia, then upper respiratory infection, and finally with community-acquired bacterial pneumonia, while the child never had any fever or upper respiratory symptoms. Failure of outpatient treatment with oral antibiotic and bronchodilator, with the persistence of respiratory symptoms such as retractions, bilateral crackles, and hypoxemia led to hospitalization for intravenous antibiotics. Given persistent symptoms, further evaluation was performed, and she was diagnosed with NEHI based on characteristic chest CT findings. Conclusions. Viral respiratory infections are the most frequent cause of respiratory illnesses in the first years of life. Primary care providers should be aware of less frequent causes of persistent respiratory symptoms in infancy like NEHI and other interstitial lung diseases in children. This may prevent unnecessary use of antibiotics and delayed diagnosis.